Notes on Nursery and Regeneration Technique of Some Species Occurring in Southern Tropical Wet Evergreen and Semi-evergreen Forests of Karnataka (India): Part-I - Raj, S. N. (Indian Forester, 1983)
Nursery and regeneration technique of nine species of Southern Tropical Wet Evergreen and Semi-evergreen Forests of Karnataka (India) has been suggested. The study was conducted in three nurseries located at different places, with different soil and rainfull. Length of roots and shoots of seedlings, selected at random, has been recorded. The root system of seedlings has been studied and described. A brief description of fruiting behaviour. Seed collection and handling, Natural and Artificial regeneration and the distribution of the species is also given. The species covered in the present study are Callophyllum elatum, Conarium strictum, Dipterocarpus turbinatus, Elaeocarpus tuberculatus, Hopea parviflora, Lophopetalum wightianum, Mesua ferrea, Persia macrantha and Vateria indica.